Two Serial Hematocrit Level Just After Admission to Predict Dengue Hemorrhagic Fever Severity - Fauziyyah Ramadhani; Mohammad Ghozali; Leni Lismayanti (Global Medical & Health Communication (GMHC), 2018)
Dengue hemorrhagic fever (DHF) is still the leading cause of hospitalization and death among children in Indonesia because of plasma leakage leading to shock syndromes. This study aimed to associate the hematocrit difference (first and second) from serial hematocrit (Hct) examination just after admission with DHF severity. A analytical cross-sectional study was involving medical records of pediatric patients with DHF admitted at the pediatric ward and the Pediatric Intensive Care Unit (PICU) of Dr. Hasan Sadikin General Hospital, Bandung in January–December 2015. The subjects excluded if other conditions also cause plasma leakage. The difference in first and second Hct (∆Hct) from serial Hct examination just after admission and DHF grade of severity (DHF I–IV) confirmed by a positive result in serologic tests (anti-dengue IgM/IgG), or detection of dengue virus antigen (NS1Ag test) obtained. Spearman association analysis test used for analysis. A total of 16 subjects with DHF I, 21 subjects with DHF II, 31 subjects with DHF III and two subjects with DHF IV included in this study. There was no significant correlation between positive ∆Hct value (hemoconcentration) and DHF severity (r=0.247, p=0.394, CI=95%). In conclusion, the difference in first and second Hct from serial Hct examination just after admission has no significant association with the disease severity. DUA NILAI HEMATOKRIT SERIAL SESAAT SETELAH ADMISI SEBAGAI PREDIKTOR KEPARAHAN DEMAM BERDARAH DENGUEDemam berdarah dengue (DBD) merupakan penyebab utama hospitalisasi dan kematian anak di Indonesia disebabkan oleh kebocoran plasma yang berujung pada syok. Tujuan penelitian ini mengetahui hubungan perbedaan hematokrit pertama dan kedua pada pemeriksaan hematokrit serial sesaat setelah admisi dengan keparahan DBD. Penelitian merupakan analytical cross-sectional study menggunakan data sekunder berupa rekam medis pasien anak yang dirawat di ruang perawatan anak dan Pediatric Intensive Care Unit (PICU) RSUP Dr. Hasan Sadikin Bandung pada Januari–Desember 2015. Subjek penelitian dieksklusi apabila pada rekam medis terdapat diagnosis lain yang menyebabkan kebocoran plasma. Variabel penelitian ini adalah perbedaan hematokrit pertama dan kedua (∆Hct) pada pemeriksaan hematokrit serial serta diagnosis DBD (DBD I–IV) yang dikonfirmasi oleh hasil positif pada pemeriksaan serologis (IgM/IgG antidengue) atau deteksi antigen virus (NS1Ag). Terdapat 16 subjek DBD I, 21 subjek DBD II, 31 subjek DBD III, dan 2 subjek DBD IV. Dengan menggunakan Uji Analisis Spearman, tidak terdapat korelasi yang signifikan antara nilai positif ∆Hct (hemokonsentrasi) dan tingkat keparahan DBD (r=0,247; p=0,394; CI=95%). Simpulan, perbedaan hematokrit pertama dan kedua pada pemeriksaan hematokrit serial tidak berhubungan dengan keparahan DBD.